Infusion medication concentrations in UK's critical care areas: Are the Intensive Care Society's recommendations being used?. (February 2017) - Titiesari, Yovita D; Barton, Greg; Borthwick, Mark; Keeling, Susan; Keeling, Peter
Following two studies done in 2007 and 2009, a follow-up of the adherence to the suggested guidelines on drug standardisation has been performed with a suggestion for future standards that can be achieved, to complement the recently published Carter report. The Intensive Care Society (ICS) introduced recommendations for infusion concentrations of 16 medications commonly used in critical care areas. The importance being improvement in patient safety and rationalised use of available critical care resources. Five years after publication of these recommendations, a further audit has been undertaken to assess the level of acceptance and application. This revealed that 89.5% of the 133 surveyed units (representing 42.49% critical care units across the UK) have adopted the recommendations. There are further medication concentrations which could also be standardised.